The Antinomy of Agrarian Reform Regulations After the Establishment of the Land Bank Authority - Bayu Praditya Herusantoso (Faculty of Law, University of Jember, Indonesia, 2024)
The establishment of the Land Bank through Government Regulation No. 64 of 2021 introduces a significant framework designed to secure land availability for public, social, national development, economic equality, land consolidation, and agrarian reform purposes. This regulation marks a new phase in agrarian reform, particularly with the introduction of Presidential Regulation 62 of 2023, which replaces earlier regulations (Nos. 88 of 2017 and 86 of 2018) to streamline and enhance the effectiveness of land reforms. Despite its mandate to allocate 30% of land for agrarian reform, the Land Bank faces challenges due to overlapping land acquisition sources, which often intersect with lands designated for agrarian reform. This research utilizes normative juridical methods to analyze these conflicts between the regulations governing the Land Bank and the enhanced framework provided by the Presidential Regulation on Acceleration of Agrarian Reform. The findings highlight a significant overlap between the targeted lands for agrarian reform and those acquired by the Land Bank. This overlap results in discrepancies in land rights among subjects of land redistribution, who are affected differently depending on whether lands are under the management rights of the Land Bank. The study suggests that legal harmonization efforts are necessary to address these conflicts, recommending the application of Lex superiori derogat legi inferiori, where higher legislation should override lower ones. Such harmonization is critical to resolve norm conflicts and ensure the equitable distribution of land rights, thereby facilitating the objectives of agrarian reform. KEYWORDS : Antinomy, Agrarian Reform, Land Bank